Energy status regulated umami compound metabolism in harvested shiitake mushrooms (Lentinus edodes) with spores triggered to release - Rongrong Xia; Xuemei Zhao; Guang Xin; Libin Sun; Heran Xu; Zhenshan Hou; Yunting Li; Yafei Wang (Food Science and Human Wellness)
The molecular mechanisms of energy status related to the umami taste of postharvest shiitake mushrooms during spore release remain poorly understood. In this study, the variations of energy status and umami taste of mushrooms were measured at 25 °C. At 24 h storage, slight spore prints of mushrooms were first pictured, respiration peaked. Significant ATP decrease and ADP increase were also observed as the initiation of postharvest senescence (P < 0.05). Meanwhile, the activities of phosphohexose isomerase, succinate dehydrogenase, glucose-6-phosphate dehydrogenase and cytochrome c oxidase and the contents of umami nucleotides and amino acids were maintained at higher levels in mushrooms with spore release. Notably, the equivalent umami concentration (EUC) was strongly correlated with energy levels (R = 0.80). Fifteen related gene expression levels in the energy metabolism pathway were downregulated. LecpdP1 and LeAK were significantly expressed in the conversion of ATP into AMP and played key roles in connecting the energy state and umami level. These results provided valuable insights on the umami taste associated with energy metabolism mechanism during postharvest mushroom spore release.